Improving communication of post-holmium laser enucleation of the prostate recovery using a surgeon-patient handout - Assmus, Mark A.; Lee, Matthew S.; Helon, Jessica; Krambeck, Amy E. (Canadian Urological Association Journal, 2022)
Introduction: To improve surgeon-patient communication of postoperative expectations, a multidisciplinary team created and evaluated a holmium laser enucleation of the prostate (HoLEP) expectations handout. Although an effective benign prostatic hyperplasia (BPH) surgery, it is crucial that patients understand the HoLEP recovery. A quality assessment previously performed at our center revealed 11% of patients were not aware of potential ejaculate volume changes. Methods: Patients presenting for consultation prior to HoLEP were assessed with post-procedure patient-reported outcomes (PRO) questionnaires before (n=50) and after (n=50) the implementation of a surgeon-patient expectations handout. Patient demographics and perioperative course were examined in the context of responses. Comparisons were made with a Chi-squared test (p<0.05). Results: We observed a response rate of 96% (pre-handout: 46/50 vs. post-handout: 50/50). Overall, 89/96 (93%) patients felt they had a reasonable understanding of HoLEP expectations, with no difference between cohorts (45/46 vs. 48/50, p=0.71). There was no difference in reporting an understanding of post-HoLEP hematuria (p=0.12) or urinary incontinence (UI) (p=0.99). The implementation of the handout improved understanding of retrograde ejaculation (pre-handout: 41/46 vs. post-handout: 50/50, p=0.022) and dysuria (pre-handout: 35/46 vs. post-handout: 46/50, p=0.048). Fifty-five patients experienced any dysuria postoperatively, with 89% reporting less than or equal to what they expected. Close to 30% (28/94) of respondents offering ways to improve communication suggested an educational website. Conclusions: The implementation of a surgeon-patient handout during HoLEP consultation improved understanding of postoperative retrograde ejaculation and dysuria at our center. We identified areas for future technology-aided improvements in post-HoLEP communication.